ANTIMICROBIAL SUSCEPTIBILITY AND DETECTION METHODS FOR THE EXTENDED‑SPECTRUM β-LACTAMASES PRODUCING ENTEROBACTERIACEAE FROM CLINICAL SAMPLES - G, Kaviyarasan; Kcp, Rajamanikandan; M, Sabarimuthu; S, Ramya; Prasanth D, Arvind (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Detection of extended-spectrum β-lactamases (ESBLs) is crucial for the infection control and antibiotic choice in healthcare settings. The aim of this study is to develop a standardized, inexpensive, and simple approach that is able to detect ESBL-producing Enterobacteriaceae isolates. Methods: Isolates those were resistant to at least one of the three indicator cephalosporins (cefotaxime, cefpodoxime, and ceftazidime) were tested for ESBL production using the double disc synergy test (DDST), combined disc synergy test (CDST) test and genotypic detection of the responsible gene for the ESBL. Result: From 64 isolates, 28 were resistant to cephalosporins. In 28 isolates, 23 were positive in CDST but in the DDST 18 were showing ESBL positive. 10 were positive in both CDST and DDST. Conclusion: Resistance to cephalosporins, which are the drug choice to treat mixed bacterial infections by the Enterobacteriaceae of which disseminate rapidly being plasmid mediated. Hence, it is necessary that rapid detection of ESBL should be done and immediate infection control measures should be implemented to prevent their dissemination.